(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study, which was designed as a case study, is to examine the possible effects of watching a math-themed movie on students’ attitudes, beliefs, emotions, and, math anxiety in math class. The research was carried out with 12 students who were enrolled in the 6th-grade in a public school in Konya. Two different math-themed movies (The Man Who Knew Infinity, Fermat’s Room) screened to the participants for the intervention, which lasted seven class hours in one week. The data of the study collected through semistructured interviews conducted with 12 students. After content analysis, the data of the research classified under five categories (self-confidence in mathematics, necessity of mathematics, ways to be successful in mathematics, math anxiety, and fun) and it was found that watching math-themed movies have a positive affect on students’ attitudes, beliefs, emotions towards mathematics, and, math anxiety. So in this paper, a promising, novel and, practical education way introduced for increasing positive beliefs, emotions, and attitudes towards mathematics and decreasing math anxiety.